Effects of Ashwagandha-derived silver nanoparticles on pre- and post-thaw semen quality in bulls - Kanwar, Arushi; Virmani, Meenakshi; Chaudhary, Kartik; Kumar, Sandeep; Lakhani, Preeti; Kumar, Rajesh; Panihar, Neeraj (Frontiers in Veterinary Science, 2026)
This study aimed to evaluate the effects of silver nanoparticle (AgNP) supplementation on bovine semen quality, with a focus on determining whether green-synthesized AgNPs derived from ethanolic Withania somnifera (ashwagandha) extract could mitigate cryopreservation-induced damage. Bovine semen samples were supplemented with AgNPs at concentrations of 10, 20, 30, 40, and 50 μg/mL. The effects on semen quality were assessed by measuring antioxidant activity, sperm motility, morphological abnormalities, acrosome integrity, and lipid peroxidation, both in fresh semen and after cryopreservation. AgNP supplementation led to a dose-dependent increase in antioxidant activity. Among the concentrations tested, 20 μg/mL produced the most significant improvements in sperm motility and a reduction in morphological abnormalities in fresh semen. This concentration also enhanced acrosome integrity and decreased lipid peroxidation, indicating protection against oxidative stress during cryopreservation. While post-thaw motility showed limited differences, pre-freezing kinematic parameters improved with AgNP supplementation, suggesting enhanced sperm quality.Green-synthesized AgNPs, particularly at 20 μg/mL, have the potential to improve bovine semen quality and reproductive performance by reducing oxidative stress and supporting sperm function. These findings suggest AgNPs as promising additives for improving livestock reproduction, with additional research needed to explore broader applications in reproductive biology and agricultural sciences.